Evaluation of Early Markers of Nephropathy in Patients with Type 2 Diabetes Mellitus - Pierina De Muro; Antonio Junior Lepedda; Gabriele Nieddu; Michela Idini; Hai Quy Tram Nguyen; Omar Lobina; Pietro Fresu; Marilena Formato (Biochemistry Research International)
Aims. T2DM often remains undiagnosed for many years because hyperglycemia develops gradually and may not produce any symptoms. As patients with T2DM are at increased risk of microvascular and macrovascular complications, the preclinical diagnosis of the state is the key point of the disease management. Methods. We evaluated parameters such as GAGs/PGs, NAG, and NGAL in urine samples from 43 normoalbuminuric T2DM patients and 31 apparently healthy control subjects. Results. The total urinary GAG excretion showed no significant differences between patients and controls. The electrophoretic analysis evidenced the presence of UTI and its degradation products (LSC and SM-LSC), CS, and HS. We observed modifications of HS and total UTI (including UTI and its degradation products) relative contents in T2DM patients compared with controls whereas no differences in CS percentage were found. NGAL levels were significantly increased in T2DM patients and were positively correlated with both NAG (r=0.606, p<0.0001) and the presence of hypertension (r=0.352, p<0.05). Conclusions. These data suggest that the assessed molecules could represent useful markers to detect early renal impairment in patients with T2DM.